Recent Advances in Supported Ionic Liquid Membrane Technology in Gas/Organic Compounds Separations - Kaur, Pawanpreet; Chopra, Harish K. (Current Organic Chemistry, 2022)
The development of the convenient separation processes is a major challenge being examined by scientists and technologists due to its industrial applications. The supported liquid membrane (SLM) technology has been widely employed to separate several species, like permeable gas from binary gaseous mixtures, metal ions, and organic and biological compounds. The main reason for the limited use of SLMs in the industry is their short life and less stability due to the high volatility of traditional organic solvents. Room-temperature ionic liquids (RTILs) are environmentally benign designer salts, exhibit negligible volatility, show good thermal stability, and have remarkable solubility, thus, acting as an alternative solvent to overcome the drawbacks of SLMs. Besides, the high viscosity of ionic liquids (ILs) offers good capillary force, which prevents their flow into membrane pores even under high pressure. Moreover, their tuned properties make them amenable compounds for their immobilization into membrane pores to provide supported ionic liquid membranes (SILMs) with good mechanical strength. In literature (from 2007 to the present), a variety of SILMs have been designed, synthesized, and employed in the field of separation science. This review is mainly focused on the applications of SILMs in the separation of more permeable gases (CO2, O2, CO, H2, and C2H4) from binary gas mixtures as well as the separation of organic compounds (organic acids, alcohols, aromatic hydrocarbons, amines, reactants and products of transesterification reaction, nitrogen- and sulfur-containing aromatic compounds) from distinct mixtures.
Keywords: membranes